Perancangan Interior Pusat Fotografi di Surabaya - Limanto, Alvin (Intra, 2015)
The reality today is that many people starting to really get into the photography world, varying from those who only wanted to try, following the trends, until those who really are serious and considering it to be a distinctive profession. Interests in the photography world nowadays are not well balanced with the sufficient knowledge about the photography itself, and it is indeed hard for the common people to acquire such information. And the fact is there is still no means available to accommodate their needs. The goal of this design is to give that means for people in Surabaya city, a place to gather together with those with common interests in photography, to share and to meet each other. The means of this interior design is recreative and commercial.Â